2020
DOI: 10.3389/fchem.2020.00077
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilically Activated Nitroalkanes in Reactions With Carbon Based Nucleophiles

Abstract: Unusual reactivity of nitroalkanes, involving formation of aci-forms (nitronic acids or nitronates) and their subsequent interaction with carbon-based nucleophiles, is surveyed in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Although nitroalkanes ( 4 ) normally behave as pronucleophilic species; in a polyphosphoric acid medium they are stabilized in a form of phosphorylated nitronates ( 5 ) with profound electrophilic properties. These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel–Crafts-type C–H functionalization reactions, often with subsequent accompanying rearrangements [ 21 , 22 , 23 , 24 ]. Furthermore, it was found that nitrogen-based nucleophiles ( 6 ), such as aliphatic amines [ 25 , 26 , 27 ], anilines [ 28 , 29 , 30 , 31 ], or hydrazines [ 32 , 33 ], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although nitroalkanes ( 4 ) normally behave as pronucleophilic species; in a polyphosphoric acid medium they are stabilized in a form of phosphorylated nitronates ( 5 ) with profound electrophilic properties. These phosphorylated nitronates tend to react with various carbon-based nucleophiles, for instance electron-rich arenes, allowing for Friedel–Crafts-type C–H functionalization reactions, often with subsequent accompanying rearrangements [ 21 , 22 , 23 , 24 ]. Furthermore, it was found that nitrogen-based nucleophiles ( 6 ), such as aliphatic amines [ 25 , 26 , 27 ], anilines [ 28 , 29 , 30 , 31 ], or hydrazines [ 32 , 33 ], can be utilized instead of water in a process mechanistically related to the classical Nef reaction [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The α-hydrogen is also acidic to attract basic reagents that are close together, and the spatial proximity undergoes an efficient reaction— similar to an intramolecular process—to afford polyfunctionalized compounds, which are referred to as a pseudo-intramolecular process [ 14 ]. The acidic hydrogen accelerates the tautomerism between nitroalkane and nitronic acid, among which the latter reveals high electrophilicity to react with carbon nucleophiles [ 15 ].…”
Section: Reactivity and Applicationmentioning
confidence: 99%
“…Over the last decade, our group has been instrumental in the development of multistep cascade transformations triggered by initial electrophilic activation of nitroalkanes in the presence of polyphosphoric acid (PPA). [13][14][15][16][17] Proposed mechanistic rationales for all these processes involve formation of a phosphorylated nitronate species as a key electrophilic intermediate. Herein, we wish to disclose our recent studies proving that formation of nitrile oxide species is also possible under the same conditions.…”
Section: Introductionmentioning
confidence: 99%